Bridging the Gap Between Library Services in Academic Libraries: A Visiting Librarian Model. Issue 4 (1st October 2016) - Xu, Jing; Zhang, Ying; Deng, Sai
ABSTRACT: This article discusses an experience of the University of Central Florida (UCF) Library when hosting a visiting librarian from Tongji University Library in Shanghai, China, in 2015. Unlike most other visiting programs in the U.S., UCF's hosting experience offers a year-long, broad-based training in several functional areas facilitated by library administration and two bilingual librarians. The initial goals were to promote dialogue and understanding between the academic systems of the two countries, and ultimately to enhance the international users' library experience in their quest to study at foreign institutions. Through describing this visiting program and discussing its findings and assessments, the authors concluded longer term visiting programs like this can benefit both the visiting and hosting libraries and bridge the gap of academic libraries across the world.